Biodiversity, Conservation and Sustainability in Biology Texbooks in Brazil - Louzada-Silva, Daniel; Carneiro, Maria Helena da Silva (Sustainability in Debate, 2014)
Eight high school biology textbook collections selected by the Brazilian National Program of Textbooks were evaluated with regards to biodiversity, conservation and sustainability concepts. The approach given to these themes differed greatly among collections, which could be explained in part by the flexible standards proposed by the Program. Besides some conceptual inaccuracies, we also detected that the thought style employed to approach biological topics was not always strictly scientific being strongly influenced by mass media and virtual information. The subject with the greater variety of approach was sustainability and all textbooks referred to subjects such as pollution, deforestation, wildfire and recycling.